2020
DOI: 10.3389/fphar.2020.614897
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol Attenuates Testosterone-Induced Benign Prostatic Hyperplasia in Rats by Modulation of Nrf2/HO-1/NFκB Axis

Abstract: Benign prostatic hyperplasia (BPH) is a serious illness affecting middle-aged and elderly male patients. It is a complication of several diseases including metabolic syndrome. BPH has been associated with inflammation and increased oxidative stress in prostatic tissues. Piceatannol (PIC) is an active natural polyhydroxylated stilbene found in many plants. It has profound anti-inflammatory as well as antioxidant activities. However, it suffers relatively poor pharmacokinetic properties. Nanoformulation is an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
(63 reference statements)
1
7
0
1
Order By: Relevance
“…These data are in agreement with the well‐known capacity of polyphenols intake in upregulating these markers in the liver and plasma (Lenquiste et al., 2015; Zhu et al., 2012). Moreover, studies reported that piceatannol could upregulate the GSH content in keratinocytes (Maruki‐Uchida et al., 2013) and to avoid the GSH depletion and catalase exhaustion promoted by testosterone in the prostate (Eid & Abdel‐Naim, 2020). A possible reason for these effects is the presence of catechol in piceatannol and (+)‐catechin.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with the well‐known capacity of polyphenols intake in upregulating these markers in the liver and plasma (Lenquiste et al., 2015; Zhu et al., 2012). Moreover, studies reported that piceatannol could upregulate the GSH content in keratinocytes (Maruki‐Uchida et al., 2013) and to avoid the GSH depletion and catalase exhaustion promoted by testosterone in the prostate (Eid & Abdel‐Naim, 2020). A possible reason for these effects is the presence of catechol in piceatannol and (+)‐catechin.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2/HO-1 pathway has been widely studied with regard to its role in combating inflammation and fibrosis [ 66 ]. In BPH, Nrf2 and its target genes have been found to be deficient and insufficient for antioxidant response [ 67 ]. Nrf2 regulates the expression of key protective elements in BPH [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that oxidative stress can aggravate the inflammatory responses via activation of NF-κB [53,54]. According to recent studies, Nrf2 regulates the expression of key protective enzymes through the antioxidant response element (ARE) in prostate cancer, and a number of its target genes are down-regulated in human prostate cancer and BPH [55]. Our results show that um-PEA/Baic treatment led to a considerable improvement in Nrf2, as well as increased HO-1 and MnSOD expression levels, suggesting the involvement of the Nrf2 antioxidant pathway in the mechanism of protection of PEA/Baic compared to the action of um-PEA, which showed only anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%